2002
DOI: 10.1001/archopht.120.12.1689
|View full text |Cite
|
Sign up to set email alerts
|

Complete Androgen Insensitivity Syndrome

Abstract: To determine whether androgen receptors affect the fatty acid profiles of neutral and polar lipids in human meibomian gland secretions.Methods: Meibomian gland secretion samples were obtained from both eyes of (1) women with complete androgen insensitivity syndrome, a condition characterized by dysfunctional androgen receptors, and (2) agematched female and male controls. Samples were processed for high-performance liquid chromatography, mass spectrometry, or both and for analysis of the mass spectra of neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(21 citation statements)
references
References 50 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…The latter statement was corroborated in direct HPLC-MS experiments with human meibum (Butovich, 2009b; Butovich et al, 2007a; Butovich et al, 2007b), in which only exceedingly small amounts of TAG, and no true DAG, have been observed. Also, the m/z values reported by Sullivan et al (Krenzer et al, 2000; Sullivan et al, 2002a) as those of major lipid analytes were too small to be the signals of actual meibomian lipids: contrary to the authors' conclusions, there are no lipids in existence with m/z values between 100 and 200 such as those reported in Tables 2 and 3 and in Fig. 3 in (Sullivan et al, 2006), and in Tables 1 and 2 in (Sullivan et al, 2002a).…”
Section: A Concept Of Meibogenesismentioning
confidence: 70%
See 2 more Smart Citations
“…The latter statement was corroborated in direct HPLC-MS experiments with human meibum (Butovich, 2009b; Butovich et al, 2007a; Butovich et al, 2007b), in which only exceedingly small amounts of TAG, and no true DAG, have been observed. Also, the m/z values reported by Sullivan et al (Krenzer et al, 2000; Sullivan et al, 2002a) as those of major lipid analytes were too small to be the signals of actual meibomian lipids: contrary to the authors' conclusions, there are no lipids in existence with m/z values between 100 and 200 such as those reported in Tables 2 and 3 and in Fig. 3 in (Sullivan et al, 2006), and in Tables 1 and 2 in (Sullivan et al, 2002a).…”
Section: A Concept Of Meibogenesismentioning
confidence: 70%
“…Also, the m/z values reported by Sullivan et al (Krenzer et al, 2000; Sullivan et al, 2002a) as those of major lipid analytes were too small to be the signals of actual meibomian lipids: contrary to the authors' conclusions, there are no lipids in existence with m/z values between 100 and 200 such as those reported in Tables 2 and 3 and in Fig. 3 in (Sullivan et al, 2006), and in Tables 1 and 2 in (Sullivan et al, 2002a). With all likelihood, those signals were either spontaneously formed fragments of actual lipids as a result of in-source fragmentation, or chemical or electronic noise generated by the instrument.…”
Section: A Concept Of Meibogenesismentioning
confidence: 70%
See 1 more Smart Citation
“…We found that androgen deficiency in humans is associated with an increase in lid keratinization and the number of occluded and metaplastic meibomian gland orifices; reduced meibum quality; altered meibum lipid patterns; a decreased tear film breakup time; enhanced corneal fluorescein and conjunctival rose bengal staining; and increased DED symptoms [62-65, 68, 69]. …”
Section: Discussionmentioning
confidence: 99%
“…We discovered that androgens stimulate the function of this tissue, including increasing its lipogenesis and suppressing its keratinization [62-65, 70-76]. Indeed, dihydrotestosterone regulates the expression of thousands of genes in human meibomian gland epithelial cells, many of which are linked to lipid- and keratin-related activities [70].…”
Section: Discussionmentioning
confidence: 99%